Older people's conceptualisation of poverty and their experiences of government programmes in Uganda. Issue 3 (3rd April 2019) - Kabuye, Rosette; Mukasa, Norman
ABSTRACT: This article explores older people's understandings of poverty and analyses their experience of government policies for fighting poverty. It employed qualitative methods, including focus group discussions and key informant interviews. A total of 120 older people in two districts in Uganda participated in the study. Based on thematic analysis and observation of non-verbal communication, older people's perspectives on poverty included a wide range of deprivations in their household. Findings reveal that there is a lack of legislation support and effective information for old people to demand accountability or influence policy strategies to address poverty. Despite the difficult living conditions of older people in poverty, the majority live independent lives, are self-reliant and use a variety of strategies to address poverty. Therefore, there is a need for scrutiny to ensure that poverty alleviation support reaches those who need it most.